Business Mathematics / Fifth Edition - Highland Esther H; Peselnick Charles; Rosenbaum Robert S (Prentice Hall, 1997)
Essential Mathematics, Percents and Their Applications, Pricing a Product, Commercial Discounts, Accounting Topics: Depreciation and Valuation of Inventory, Accounting Topics: Parthnership and Profits and Payroll, Borrowing Money: Interest, Borrowing Money: Bank Discounts, Consumer Profit, Compound Interest, Annuities, Understanding Statistics, Investing, Appendices, Review of Arithmentic, The Metric System, Tables, Answers to Odd-Numbered Problems, Index.